2019
DOI: 10.25226/bboc.v139i3.2019.a3
|View full text |Cite
|
Sign up to set email alerts
|

Galliform diversity in south-west Yunnan, China, with notes on Blood Pheasant Ithaginis cruentus and White Eared Pheasant Crossoptilon crossoptilon biology

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
2
3
1
Order By: Relevance
“…Our findings indicated that in the QMNNR, BP was found lower (2600-3300 m a.s.l.) than those in previous studies [19,74] but similar to the elevations (2400-3800 m a.s.l.) in Wanglang and Wolong in Sichuan Province [75].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings indicated that in the QMNNR, BP was found lower (2600-3300 m a.s.l.) than those in previous studies [19,74] but similar to the elevations (2400-3800 m a.s.l.) in Wanglang and Wolong in Sichuan Province [75].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, random sampling for 24 h per day captured the natural diel activity pattern of the species in as unbiased a manner as possible [4,39]. Diel activity patterns of both species were bimodal in breeding and non-breeding seasons, which were generally consistent with previous studies [17,58,74,75]. However, they showed a unimodal pattern in winter.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Peacock-pheasants, Silver Pheasants) encountered less frequently, especially as legal access to most protected forests is now largely restricted for local communities. Such species are also often shy and elusive (especially due to hunting) and are known to be under-counted by observers and challenging to detect without camera traps (Brooks et al 2019, Xu et al 2019). Variation in species detectability (e.g.…”
Section: Discussionmentioning
confidence: 99%